'On Consulting the Faithful' in Matters of Human Identity, Sexuality and Gender. Issue 1 (1st January 2021) - Beardsley, Christina
Abstract : This article considers a perceived gap between Church of England House of Bishops' statements on human identity, sexuality and gender, and the outlook of many congregations. It does this under five headings suggested by a brief study of St John Henry Newman's On Consulting the Faithful in Matters of Doctrine . Topics are the bishops' teaching responsibilities, how doctrinal consultation works in the Church of England, the tendency to prioritise church unity and the role of formation and of emotion. It concludes that the Church of England's protracted conversations on sexuality should be resolved in a General Synod debate on equal marriage.